Поняття та зміст права на життя - Старко, О.; Starko, O. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті досліджено проблеми права людини на життя. Проаналізовано питання поняття права на життя. З’ясовано сутність змістових елементів права на життя, а саме права-поведінки, права-вимоги, права-користування й права-домагання. Розглянуто проблему евтаназії, часових меж права на життя, запропоновано внесення змін до чинного законодавства.The article deals with the right to life. The concept of the right to life is analyzed. The essence of elements containing the right to life are detected, namely rightsconducts, rights-requirements, rights-of-use and rights-claims. The right-behavior involves human activities directed at ensuring the safety of the biological existence. The right-requirement is that the person has the right to demand from the government, international organizations and society the implementation of the commitments for life ensuring. The right-use is an ability to be free to enjoy the life in conditions of personal safety. The right-claim is an ability to contact the national law enforcement agencies and international organizations to protect their inalienable right to life. The problem of temporal limits of the right to life and the problem of euthanasia are examined. An addition for several rules of law of the current legislation is suggested.
The Concept and The Content of The Right to Life.
Keywords: життя; право людини на життя; евтаназія; life; the right to life; euthanasia